An Overview of Knowledge Levels about Organ Topography and Structure among Grade IV Medical Students - Yuniarti Yuniarti; Rizki Perdana; Ariko Rahmat Putra; Fajar Awalia Yulianto; Muhammad Agie Najibullah Wijaya; Wendy Darmawan (Global Medical & Health Communication (GMHC), 2021)
One of the competencies the students of the graduate medical education is to apply the basic principles of the science of biomedicine, epidemiology, clinical, and behavior in the practice of medicine. Anatomy is one of the biomedicine sciences learned in medical education, including learning about the body's structure and organ topography. This research aims to describe the organ's structure and topography knowledge among the faculty of medicine students. This survey with 88 students was conducted in a faculty of medicine in Bandung city from October to December 2018 using a random sampling method. Statistical analysis using frequency distribution, percentage proportions, and Wald's statistics in the 95% confidence interval. The instrument for validity analysis is Pearsons's correlation, and the instrument for reliability analysis is Kappa's percent agreement. The results showed the average level of knowledge on organ structure and topography. It shows anatomical teaching and learning about the organ's structure, and the topography still needs to be optimized. GAMBARAN TINGKAT PENGETAHUAN TENTANG STRUKTUR DAN TOPOGRAFI ORGAN PADA MAHASISWA TINGKAT IV KEDOKTERANSalah satu kompetensi lulusan mahasiswa pendidikan kedokteran adalah mampu mengaplikasikan prinsip ilmu dasar biomedik, epidemiologi, klinis, dan perilaku dalam praktik profesi kedokteran. Anatomi merupakan salah satu ilmu biomedik dalam pendidikan kedokteran yang mempelajari struktur dan topografi organ. Penelitian ini bertujuan mengetahui tingkat pengetahuan mahasiswa tingkat IV fakultas kedokteran mengenai struktur dan topografi organ. Survei terhadap 88 mahasiswa ini dilaksanakan di sebuah fakultas kedokteran di Kota Bandung dari bulan Oktober hingga Desember 2018 menggunakan metode random sampling. Analisis statistik menggunakan distribusi frekuensi, persentase proporsi, dan Wald’s statistic dalam 95% interval kepercayaan. Analisis validitas menggunakan Pearson’s correlation, sedangkan analisis reliabilitas menggunakan Kappa’s percent agreement. Hasil penelitian menunjukkan tingkat pengetahuan rerata tentang struktur organ dan topografi dalam kategori cukup. Hal ini menunjukkan pembelajaran anatomi tentang struktur organ dan topografi masih perlu dioptimalkan.